Preparation of PTT/clay nanocomposites with solid‐state polymerized polytrimethylene terephthalate. Issue 3 (8th May 2012) - Engelmann, G.; Bonatz, E.; Ganster, J.; Pinnow, M.; Bohn, A.
Abstract: To enhance the effectiveness of polytrimethylene terephthalate (PTT) for the preparation of clay‐based nanocomposites by melt intercalation and to upgrade the mechanical performance of these materials, solid‐state‐polymerization (SSP) experiments with neat PTT were carried out at 190, 200, and 210°C prior compounding to increase the average molecular weight and, based on this, the melt viscosity of this polymer. The progress of SSP was registered by time dependent sampling of intrinsic viscosity data. From this, activation energy of 180.6 kJ mol −1 was calculated. A characteristic sublimate formed during these SSP‐reactions was identified by mass‐spectroscopy to be a mixture of cyclic oligomers containing 2, 3, 4, and 5 monomeric units. The melt viscosity of neat PTT(SSP) could be increased from ∼ 460 to 15, 000 Pa s −1 . Therefore, tensile strength and Young's modulus were improved by 3.5 and 9%, respectively. Manufacturing of PTT(SSP) and the modified nanoclay was carried out with a corotating twin‐screw‐extruder at 230°C. A concentration of 3% of the inorganic filler component in the composites was aimed at. Compared with the data of virgin PTT, tensile strength, and modulus of the PTT(SSP)‐based nanocomposites could be enhanced by ∼ 9 and 40%, respectively. Additionally, a SSP‐reaction of the nanocomposite prepared with non‐pretreated PTT and nanoclay was performed at 210°C to test the robustness of the matrix polymer PTT against the influences of the nanofiller. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :